2016
DOI: 10.1186/s13223-016-0155-8
|View full text |Cite
|
Sign up to set email alerts
|

Interacting effects of obesity, race, ethnicity and sex on the incidence and control of adult-onset asthma

Abstract: BackgroundTo improve care and control for patients with adult-onset asthma, a better understanding of determinants of their risk and outcomes is important. We investigated how associations between asthma, asthma control and obesity may be modified by patient demographic characteristics.MethodsThis retrospective study of adults enrolled in several health plans across the U.S. (n = 2,860,305) examined the interacting effects of obesity, age, race, and sex on adult-onset asthma and asthma control. Multivariable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 43 publications
2
25
1
2
Order By: Relevance
“…However, intriguingly, logistic regression analysis demonstrated a significant positive relationship. Previous studies reported that one of the important risk factors for asthma in women is being overweight or obese [21][22][23][24][25]. Furthermore, smoking contributes to the development of asthma in men and women [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, intriguingly, logistic regression analysis demonstrated a significant positive relationship. Previous studies reported that one of the important risk factors for asthma in women is being overweight or obese [21][22][23][24][25]. Furthermore, smoking contributes to the development of asthma in men and women [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Various biological and nonbiological mechanisms have been proposed to explain the relationship between obesity and poor asthma control. These include decreased response to corticosteroids, the effect of some immunomodulatory adipokines, the change in pulmonary dynamics, low levels of vitamin D, and obesity-related comorbidities such as gastroesophageal reflux and depression [46,60,61]. Gastroesophageal reflux is also a common comorbidity in obese children and is responsible for worse asthma control [36].…”
Section: Should Obesity Be Taken Into Account In the Diagnosis And Fomentioning
confidence: 99%
“…В отдель-ных работах та же тенденция отмечена у мальчиков, больных бронхиальной астмой [26]. У взрослых паци-ентов ожирение встречается чаще у женщин с бронхи-альной астмой, чем у мужчин [27][28][29].…”
Section: результаты и обсуждениеunclassified